Severe Burns and Amputation of Both Arms in the First Psychotic Episode of a Schizophrenic Patient - Cruzado, Lizardo; Villafane-Alva, Ronald; Caballero-Atencio, Katia; Cortez-Vergara, Carla; Núñez-Moscoso, Patricia (Case Reports in Psychiatry, 2015)
An alleged reduction of sensitivity to pain in people with schizophrenia has been reported, but the nature of this complex phenomenon has not been elucidated yet. Reports of insensitivity to burns from people with schizophrenia are extremely rare. We report the case of a 24-year-old man who set both of his arms on fire during the first break of paranoid schizophrenia. As a result of severe tissue damage, both of his limbs had to be amputated. Today, at the age of 59, the patient is physically and mentally rehabilitated and is adherent to treatment. Additionally, given the uncertainty about the true nature of the alleged hypoalgesia in schizophrenia, we postulate the need for a comprehensive phenomenological approach in the study of embodiment in people with this condition.